Experiencias relacionadas con la implementación de políticas de inclusión social en educación a distancia (2015)
In the following article, a theoretical framework is intended to identify those theoretical approaches that sustain the subject of social inclusion in post-secondary education through distance learning. For this, a data research was carried out and grouped into three blocks: the first one related to inclusive education and social inclusion. The second one related to the politics that support them in all the countries of Latin America as Mexico, Argentina, Brazil, Chile and finally Colombia. The third one is about the distance learning and the definition of inclusion. It could be determined that even though there have been several politics research and strategies it is mandatory to keep creating educational environment inwhich people can appreciate and respect the differences.